The Effect of Teacher Personality Competence on High School Students' Learning Motivation - Mardelita, Fega Priti; Mutathahirin, Mutathahirin; Rambe, Anggi Afrina; Panyahatan, Nasbin; Defrinal, Defrinal; Bimantoro, Rizal Tri (Sekolah Tinggi Agama Islam YDI Lubuk Sikaping, 2023)
The personality competence of teachers plays a crucial role in shaping students' learning experiences and motivation. This study aims to analyze the personality competence of Islamic religious education teachers at Senior High Schools and its correlation with student learning motivation. This research is field research with a quantitative method that uses a correlational approach, aiming to determine whether there is a relationship between two variables. The sample in this study consisted of 176 students, with 25% of the population 44 students selected through simple random sampling to ensure equal opportunity for all students to be sampled. Based on the results of data analysis obtained using descriptive statistics, the personality competence of Islamic education teachers is in the quite high category, at 34.1%. Furthermore, a correlation exists between the personality competence of Islamic education teachers and student learning motivation, assessed using the pearson product moment correlation test. The correlation value is 0.312. These results indicate that the correlation between the personality competence of Islamic education teachers and student learning motivation is significant, as the calculated